Advanced array systems, applications and RF technologies - Fourikis, Nicholas (Signal processing and its applications., 2000)
Advanced Array Systems, Applications and RF Technologies adopts a holistic view of arrays used in radar, electronic warfare, communications, remote sensing and radioastronomy. Radio frequency (RF) and intermediate frequency (IF) signal processing is assuming a fundamental importance, owing to its increasing ability to multiply a system's capabilities in a cost-effective manner. This book comprehensively covers the important front-end RF subsystems of active phased arrays, so offering array designers new and exciting opportunities in signal processing. Key Features * provides an up to date record of existing systems from different applications * explores array systems under development * bridges the gap between textbook coverage of idealized phased arrays and practical knowledge of working phased arrays * recognises the significance of cost to the realization of phased arrays * discusses future advances in the field that promise to deliver even more affordable arrays ['intelligent' or self-focussing/-cohering arrays].